Reconciling civilizations: eliciting residents’ attitude and behaviours for international Muslim tourism and development - Han, Heesup; Al-Ansi, Amr; Chua, Bee-Lia; Ahmad, Naveed; Kim, Jinkyung Jenny; Radic, Aleksandar; Ryu, Hyungseo Bobby (Routledge, 2022)
This research was designed to depict the process of generating approach behaviours for Korean and US residents for Muslim travellers. Through a quantitative procedure, the built frameworks explicated a sufficient amount of the variance in attitude, emotions and approach behaviours. Benefit perception, Islamic knowledge, social norm, image and Islamophobia were essential components of the developed frameworks. The mediating nature of resident attitude and emotions were evident. The Islamic knowledge and attitude relation and the emotion and approach behaviour relation differed across Korean and US residents. The comparative importance of resident attitude in developing approach behaviours was uncovered in both groups.